Dept. H : pressure - Kindt, Matt (Dark Horse Books, 2017)
"A special investigator hired to uncover possible sabotage taking place at a deep-sea research station uncovers a crime scene filled with suspects with terrible secrets, strange deep-sea creatures, and an impending flood"--